Vernicia fordii (Hemsl.) Airy Shaw extract stimulates insulin secretion in pancreatic β-cells and improves insulin sensitivity in diabetic mice. (5th October 2021) - Hyun, Jimin; Park, Mi Hyeon; Lee, Yo Han; Lee, Youngeun; Jeong, Su Ji; Choi, Sun Sil; Khim, Keon Woo; Eom, Hye Jin; Hur, Jin-Hoe; Park, Chan Young; Kim, Jae-Ick; Park, Jiyoung; et al.
Abstract: Ethnopharmacological relevance: Vernicia fordii (Hemsl.) Airy Shaw ( V. fordii ) is also known as the tung tree and its leaves and fruit are used as an oriental treatment for dyspepsia, edema, and skin diseases, which are known as diabetic complications. Aim of the study: In this study, we aimed to investigate the methanolic extract (VF5) of the leaves of V. fordii as an insulin secretagogue and its probable mechanism and verify the effect in HFD-fed mice. Materials and methods: The insulin secretagogue activity of different doses of VF5 (0.1, 0.3 and 1.0 μg/ml) was assessed using in vitro insulin secretion assay and confirmed the anti-diabetic effect in mice fed HFD for 4 weeks with different doses of VF5 (10, 20 and 50 mg/kg oral) for another 6 weeks. Glbenclamide (30 mg/kg, oral) was used as positive control drug. The possible mechanisms were evaluated by using Gö6983 (10 μM), U73122 (10 μM) and nifedipine (10 μM). The major constituents of VF5 were analyzed by UPLC-QToF-MS and 1 H and 13 C NMR spectroscopy. Results: UPLC-QToF-MS and NMR spectroscopy analysis indicated that one of the main active components of VF5 was tigliane-diterpene esters. VF5 functioned as an insulin secretagogue and enhanced mitochondria respiration and insulin homeostasis. We confirmed that VF5 preserved the β-cell and reduced the β-cell expansion which caused by metabolic stress under HFD. The antidiabetic role of VF5 in HFD fed mice was assessed by glucose tolerance test (GTT) and insulin tolerance test (ITT), fasting plasma insulin level, fasting blood glucose level, AKT signal in peripheral tissue in the absence of toxic effects. Mechanistically, insulinotropic effect of VF5 was mediated by activation of PKCα via intracellular Ca 2+ influx and enhanced mitochondria function. Conclusion: VF5 exhibits potent insulin secretagogue function and improves insulin sensitivity and protection of pancreatic β-cells from metabolic stress without toxicity. Taken together, our study suggests that VF5 could be potentially used for treating diabetes and metabolic diseases through improving β-cell function. Graphical abstract: Image 1 Highlights: Vernicia fordii (Hemsl.) Airy Shaw extract (VF5) exerts insulinotropic activity. VF5 activates Ca 2+ -dependent PKCα and enhances mitochondrial function. VF5 lowers blood glucose levels by inducing GSIS in vivo. VF5 improves insulin sensitivity in diet-induced diabetic mouse model.